Effects of Intravenous Apo A-I, HDLs and Apo A-I/Phospholipid Discs on Vascular Metabolism and Atherosclerosis in Animals and Humans - Miller, N. E.; Nanjee, M. N.; Miller, I. P.; Brinton, E. A. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
High-density lipoproteins (HDLs) have several metabolic actions in vitro that are potentially anti-atherogenic. In addition to their role in reverse cholesterol transport, native HDLs have been shown to protect low-density lipoproteins (LDLs) against oxidative modification, to have anti-inflammatory properties, and to inhibit platelet aggregation. These actions have been shown to occur also in vivo in both experimental animals and humans, when plasma HDL concentration is raised by intravenous infusion of native HDLs or reconstituted discoidal particles composed of the major HDL protein, apolipoprotein (apo) A-I, in association with phosphatidylcholine (PC) and, in the case of protection of LDLs against oxidative change, by lipid-free apo A-I and apo A-I mimetic polypeptides. Intravenous infusion of native HDLs, lipid-free apo A-I and apo A-I/PC discs, and oral administration of apo A-I peptides, have been found to prevent or reverse experimentally induced atherosclerosis in animals. A mutant form of apo A-I discovered in Italy (apo A-IMilano), the biological properties of which differ somewhat from those of normal apo A-I appears to be even more potent in this regard. The hope that this approach will provide a new effective therapy for atherosclerosis has been supported by a multi-center clinical trial, in which five weekly infusions of apo A-IMilano/PC discs induced significant regression of coronary lesions, as quantified by intravascular ultrasound, in men with clinical coronary heart disease. This article reviews the data from animal and human studies in this rapidly developing area.
Keywords: atherosclerosis